Sulfonylureas Use Is Not Associated With Increased Infarct Size in Patients With Type 2 Diabetes and ST-Segment Elevation Myocardial Infarction - Shi, Fang-Hong; Li, Hao; Kong, Ling-Cong; Shen, Long; Jiang, Yi-Hong; Gu, Zhi-Chun; Ge, Heng (Frontiers in Cardiovascular Medicine, 2021)
Aims: This retrospective study assessed the association between sulfonylureas use and infarct size in patients with type 2 diabetes (T2DM) and ST-segment elevation myocardial infarction (STEMI) by myocardial enzymology indexes and cardiac magnetic resonance (CMR) imaging. Methods: Patients presenting STEMI between Jul 2013 and Aug 2019 were included in a retrospective database at our institution. Antidiabetic agents used before STEMI were recorded. Patients with maximum recorded troponin I (max cTNI) and creatine phosphokinase isoenzyme (CK-MB) within the first 72h of chest pain onset were collected. Infarct size was quantified by CMR imaging, and cardiovascular outcomes were also obtained at 30 days and 6 months follow-up. Multivariable regression models explored potential risk factors associated with infarct size and clinical outcomes. Results: A total of 254 T2DM and STEMI patients were included, with 101 sulfonylurea users and 153 non-users. Sulfonylureas users were not associated with higher max cTnI and max CK-MB compared to non-users. Among 65 CMR patients, no significant differences in infarct size were detected between sulfonylureas users and non-users. Whereas the incidence of microvascular obstruction (MVO) was higher in patients receiving sulfonylureas than those taking non-sulfonylureas (88.0% versus 62.5%, p = 0.023). No higher cardiovascular events of sulfonylureas users versus non-users were observed, except for heart failure events (24.0% versus 2.5% at 30 days, p = 0.011; 28.0% versus 2.5% at 6 months, p = 0.004). Multivariable regression analyses verified that sulfonylureas users increased the risks of MVO. Conclusions: Sulfonylureas use did not associate with larger infarct size in patients with T2DM and STEMI. A potentially higher incidence of MVO in sulfonylurea users was found. Notably, since most patients presented after a relatively long period of ischemia and glibenclamide was not used by the included patients in this observational study, the results of this study should not be extrapolated to clinical settings with short periods of ischemia or to patients using glibenclamide.